2022
DOI: 10.1155/2022/8213321
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Meets Whole Slide Images: Deep Learning Model Shapes an Immune-Hot Tumor and Guides Precision Therapy in Bladder Cancer

Abstract: Background. To construct and validate a deep learning cluster from whole slide images (WSI) for depicting the immunophenotypes and functional heterogeneity of the tumor microenvironment (TME) in patients with bladder cancer (BLCA) and to explore an artificial intelligence (AI) score to explore the underlying biological pathways in the developed WSI cluster. Methods. In this study, the WSI cluster was constructed based on a deep learning procedure. Further rerecognition of TME features in pathological images wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A considerable number of investigations have also employed variations of CNN, often categorized under the umbrella term of general deep learning. This group includes diverse studies by Liang et al [ 55 ], Zheng et al [ 49 ], and Jiang et al [ 48 ]. Residual networks, a form of CNN, have been frequently implemented, as seen in works by Liu et al [ 69 ], Wu et al [ 72 ], and Knuutila et al [ 76 ], who utilized the ResNet model due to its ability to effectively train very deep neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable number of investigations have also employed variations of CNN, often categorized under the umbrella term of general deep learning. This group includes diverse studies by Liang et al [ 55 ], Zheng et al [ 49 ], and Jiang et al [ 48 ]. Residual networks, a form of CNN, have been frequently implemented, as seen in works by Liu et al [ 69 ], Wu et al [ 72 ], and Knuutila et al [ 76 ], who utilized the ResNet model due to its ability to effectively train very deep neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…A primary challenge is the variance in data quality, which is an issue pervasive across all medical imaging analyses [ 48 , 70 ]. A broad range of factors including staining inconsistencies, scanning variations, and differences in slide preparation methodologies can induce a significant level of noise in the data, posing difficulties for the robustness of deep learning models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report is inconsistent with our results, which needs to be con rmed by subsequent studies. This may be the reason for the small sample size in GEO database.It has been reported that the degree of in ltration of suppressive immune cells in the tumor microenvironment, lifting the immunosuppressive tumor microenvironment, turning "cold tumor" into "hot tumor" to enhance anti-tumor immunity [13,24]. In addition, we investigated the relationship between the expression of key genes and immune cells in pituitary tumors, which may provide new clinical guidance for cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of precise identification of MIBC patients who are most likely to achieve optimal outcomes with neoadjuvant checkpoint inhibitor therapy, either as monotherapy or in conjunction with NAC, cannot be overstated in guiding future treatment approaches. Given the enormous amount of information in recent years, using “multi-omics” analysis, differences in intratumor environment, and heterogeneity, artificial intelligence may appear to be a “game changer” to model and tailor treatment in the near future [ 64 , 65 ].The molecular classification of UC has not yet been officially approved by any oncology society and remains unstandardized, as several groups have created nomenclatures that may be confusing and unsuitable for clinical utilization. There is a need for consensus that takes into account molecular, biological, clinical, and prognostic features of tumors, with close cooperation between expert societies (e.g., EAU, AUA) based on well-designed clinical trials and evidence-based medicine.…”
Section: Discussionmentioning
confidence: 99%